Intermittent ground-fault modeling with EMTP/ATP - Kwapisz, A.; Lorenc, J.; Staszak, B. (Видавництво Національного університету «Львівська політехніка», 2007)
This paper describe intermittent fault modeling methods used to obtain zero-sequence voltage and current waves used at development stage and test stage of the electrical power automatics devices for medium voltage network protection. The models of the fault for the lab test and digital simulation are presented. The results of transient simulation and field tests are shown.